Trends in Publication of Negative Studies in Prominent Indian Medical Journals - Arvind Singh Panwar; Aseem Saxena; Jaikaran Charan (Medsci Publications, 2021)
Background: Publication of negative studies is as important as positive studies as absence of one may lead to publication bias. Available data based on very few published studies suggests a very strong publication bias for publication of only positive studies and declining trends for publication of negative studies. In spite of a thorough review similar data on trend analysis of publication of negative studies for Indian Medical Journals could not be found. Present study is an attempt to estimate the prevalence and trends in publication of negative studies in selected Indian Medical Journals. Materials and Methods: Indian clinical practice and clinical specialties journals having an impact factor (Indexed in SCI) with publication history of 12 years or more were included in the analysis. A total of 12 journals were eligible for the inclusion. All the original articles published in these journals were analysed and studies were labeled as negative or positive based on predefined criteria. Statistics: Descriptive statistics was reported in the form of frequency, percentage and 95%CI. Fisher exact test was used for comparison of categorical variable and excel was used for linear regression and trend. Results: Out of total 6341 articles published in amongst these 12 journals between year 2000 to 2011, 284 (4.4%, 95% CI 4.0% to 5.0%) were negative studies. Slight positive trend in the publication of negative studies was observed. It was observed that there were significantly more negative studies were published in the journals having impact factor >1 as compared to journals having impact factor <1 (151/4415 Vs 133/1926, Fisher exact P =0.0000001). Conclusion: Prevalence and trend of publication of negative studies in prominent Indian Medical Journal shows strong publication bias that needs to be addressed on priority at various levels.